Pathways : J. R. Smallwood - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1983)
In this episode of Pathways Cathy Boak interviews former Premier of Newfoundland, Joseph (Joey) Smallwood. "A Memorial University Television Production, ©1983"